Issues of letter of credit in Malaysian Islamic banks - Sharifah Faigah Syed Alwi; Ismah Osman; Mohd Bahroddin Badri; Amirul Afif Muhamat; Ruhaini Muda; Uzaimah Ibrahim (Journal of Risk and Financial Management, 2022)
This paper discussed the prevailing issues currently faced by Islamic banks on the offering of Letter of Credit (LC), originally brought forward by the International Chamber of Commerce, using Shariah contracts and puts forth recommendations on practical solutions to solve the issues. The study adopted a qualitative method where the information on the issues of Islamic LCs was gathered throughout interviews with different bankers closely involved in LC issuance from 12 Islamic banks in Malaysia. The results indicate that there are three vital issues related to LCs offered by Islamic banks which lead to Shariah non-compliance issues. The issues revolve around the conversion of LC Wakalah (agency) to LC Murabahah (cost-plus), the existence of a sale contract between the customer and exporter and lastly the title of goods stated in the bill of lading. The findings recommend several solutions in relation to LCs within the underlying Shariah contracts to ensure that their operation complies with the Shariah requirements and Malaysian laws, standards and regulations. This paper highlights the issues of Islamic LC yet to be discussed thoroughly based on the views of a panel of experts and Islamic bankers.
Keywords: 650; Islamic banks; Islamic finance; issues; letter of credit; Malaysia